Immunomodulatory effect of Rhaphidophora korthalsii on mice splenocyte, thymocyte and bone marrow cell proliferation and cytokine expression - Yeap, Swee Keong; Omar, Abdul Rahman; Ho, Wan Yong; Beh, Boon Kee; Ali, Abdul Manaf; Mohammed Alitheen, Noorjahan Banu (Academic Journals, 2011)
Rhaphidophora korthalsii methanol extract was previously found as a potential in vitro immunomodulating agent. In this study, the in vitro immunomodulatory activity of R. korthalsii methanol extract on mice splenocyte were quantified through evaluating T/NK cell population, cytokine expression (IL-2 and IFN-) and cytotoxicity against Yac-1 cell. In vitro MTT proliferation study showed that R. korthalsii methanol extract stimulate significant proliferation of splenocyte, thymocyte and bone marrow cell at 25 g/ml after 72 h incubation as compared to rIL-2. Besides, 25 g/ml of extract also enhanced T-helper 1 cytokine (IL-2 and IFN-) secretion, natural killer cell (NK1.1+CD3-) population and cytotoxicity against natural killer sensitive Yac-1 leukemic cell line. It was concluded that R. korthalsii methanol extract is a potential immunomodulator agent that could activate the natural killer cell.